Preparation method and application of porous selenium-zinc oxide core-shell nanocomposite

By preparing porous selenium-zinc oxide core-shell nanocomposites, the problem of difficulty in achieving controlled release of nanoselenium and limited antibacterial effects alone is solved, and the sustained release of selenium and the synergistic antibacterial effect of zinc oxide is achieved, with long-term antibacterial effect and Good biocompatibility.

CN119404859APending Publication Date: 2025-02-11SHANGHAI SIXTH PEOPLES HOSPITAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411561455.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The safety limits between optimal concentration and toxic concentration are very narrow, and existing nanoselenium is difficult to achieve effective controlled release, and the antibacterial effect of nanoselenium and zinc oxide is limited when used alone.

Method used

Cu2-xSe oxidized by the preparation method of porous selenium-zinc oxide core-shell nanocomposite material is prepared by mixing oleic acid and selenium powder, dispersing of CuCl, injecting Se precursor solution, ethanol washing and n-hexane dispersion. The alkyl dispersion solution was then added, and deionized water, n-hexanol, trolaton X-100, n-hexane and tetraethyl silicate solutions were formed to form Se@SiO2 nanocore-shell particles, and finally through the reaction of NaOH, zinc acetate and ethanol. Selenium-zinc oxide core-shell nanocomposite was prepared.

Benefits of technology

The sustained release of selenium is achieved to reduce toxic side effects. After decomposition of zinc oxide, it has a long-term antibacterial effect, and is simple in preparation, good biocompatible, and has excellent antibacterial effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404859A_ABST
    Figure CN119404859A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a porous selenium-zinc oxide core-shell nano composite material and application of the porous selenium-zinc oxide core-shell nano composite material in antibacterial drugs. The preparation method comprises the following steps: preparing a Cu2-xSe normal hexane dispersion liquid; se (at) SiO2 nano core-shell particles are prepared; the preparation method comprises the following steps: dispersing Se-coated SiO2 nano core-shell particles in ethanol to prepare Se-coated SiO2 ethanol dispersion liquid; the preparation method comprises the following steps: uniformly mixing NaOH, zinc acetate and ethanol, adding the Se-coated SiO2 ethanol dispersion liquid, stirring, carrying out ultrasonic treatment, carrying out a heating reaction, centrifuging and washing to prepare the selenium-zinc oxide core-shell nano composite material. The synergistic antibacterial effect of selenium and zinc oxide is exerted, after the selenium-zinc oxide core-shell nanocomposite reaches a designated position, zinc oxide is decomposed, pore channels blocked by zinc oxide are opened, nano-selenium can be slowly released through the pore channels and exerts the synergistic antibacterial effect with zinc oxide, and slow release of selenium reduces the toxic and side effects of nano-selenium, so that the nano-selenium core-shell nanocomposite has a good antibacterial effect. The long-acting antibacterial effect is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a nano composite material, in particular to a preparation method and application of a selenium-zinc oxide core-shell nano composite material. Background Art

[0002] Selenium is one of the essential trace elements for the human body. Studies have shown that a lack of selenium in the human body can easily lead to many diseases such as cancer, heart disease, and diabetes. An appropriate intake of selenium has the effects of enhancing the body's immunity and delaying biological aging. However, the safety limit between the optimal concentration and the toxic concentration of selenium is very narrow, so the development of low-toxic and efficient selenium sources is very important for human health. Compared with other states of selenium, nano-selenium has the advantages of low toxicity and good bioavailability, so the development of nano-selenium-related therapeutic agents is a hot topic.

[0003] Due to the abuse of antibiotics, multidrug-resistant bacteria have emerged at an unprecedented rate around the world and are a serious threat to human health, especially Staphylococcus aureus infections, which are difficult to treat. Studies have found that nano-selenium not only has an inhibitory effect on Staphylococcus aureus, but also inhibits the activity of Aspergillus fumigatus and Candida albicans (Progress in Biotechnology, 2017, 7(5):518). It is also a traditional antibacterial agent. Humans have long learned to use zinc oxide as a coating or topical medicine. Nano zinc oxide also has antibacterial and anti-inflammatory effects. It is the safest and most effective ingredient in the evaluation of sunscreens in almost all countries. However, their extremely small size makes them more chemically active, so they are highly valued in terms of antibacterial properties.

[0004] At present, there have been many studies on the synthesis and antibacterial effects of nano-selenium and zinc oxide. However, a single antibacterial agent is difficult to meet the current antibacterial needs, especially with the emergence of super bacteria, which requires multiple ways of synergistic antibacterial effects. Therefore, it is very important to give full play to the synergistic antibacterial effects of nano-selenium and zinc oxide to meet clinical needs. Existing nano-selenium is difficult to achieve effective controlled release and its toxicity is difficult to control. Summary of the invention

[0005] The technical problems to be solved by the present invention are: the safety limit between the optimal concentration and the toxic concentration of selenium is very narrow, the existing nano-selenium is difficult to achieve effective controlled release, and nano-selenium and zinc oxide both have antibacterial effects when used alone, but the antibacterial effect is limited when used alone.

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a porous selenium-zinc oxide core-shell nanocomposite material, comprising the following steps:

[0007] Step 1): oleic acid and selenium powder are mixed to obtain a Se precursor solution, CuCl is dispersed in oleic acid and oleylamine to obtain a CuCl mixed solution, the Se precursor solution is injected into the CuCl mixed solution, ethanol is added after the reaction, the mixture is washed with ethanol and collected by centrifugation, and dispersed in n-hexane to obtain Cu 2-x Se n-hexane dispersion;

[0008] Step 2): Cu 2-x Deionized water, n-hexanol, Triton X-100 and n-hexane were added to the Se n-hexane dispersion. After the solution became clear, tetraethyl silicate solution and ammonia water were added dropwise. After the reaction was completed, the dispersion was washed with ethanol, centrifuged and dried to obtain Se@SiO2 nano core-shell particles.

[0009] Step 3): dispersing Se@SiO2 nano core-shell particles in ethanol to prepare Se@SiO2 ethanol dispersion;

[0010] Step 4): NaOH, zinc acetate and ethanol are mixed, and then Se@SiO2 ethanol dispersion is added, stirred, ultrasonicated, heated for reaction, centrifuged and washed to obtain a selenium-zinc oxide core-shell nanocomposite material.

[0011] Preferably, in step 1), Cu 2-x The concentration of Se n-hexane dispersion is 10 to 800 mg / mL.

[0012] Preferably, in step 2), Cu 2-x The volume ratio of Se n-hexane dispersion, deionized water, n-hexanol, Triton X-100, n-hexane, tetraethyl silicate solution and ammonia water is 10: 0.01-2: 1-10: 1-10: 5-100: 2-0.05: 2-0.01, and the mass concentration of ammonia water is 25-28%.

[0013] Preferably, in step 3), the concentration of the Se@SiO2 ethanol dispersion is 0.5-10 g / L.

[0014] Preferably, in step 4), the ratio of NaOH, zinc acetate, ethanol and Se@SiO2 ethanol dispersion is 0.1-1 g: 0.2-2 g: 5-200 mL: 10-300 mL.

[0015] Preferably, in step 4), the ultrasonication time is 1 to 10 minutes.

[0016] Preferably, in step 4), the heating reaction temperature is 40 to 76° C. and the time is 0.5 to 12 h.

[0017] The present invention also provides a porous selenium-zinc oxide core-shell nanocomposite material prepared by the above preparation method. The selenium-zinc oxide core-shell nanocomposite material is a composite structure in which zinc oxide coats silicon dioxide spheres, and silicon dioxide spheres coat elemental Se.

[0018] The present invention also provides the use of the porous selenium-zinc oxide core-shell nanocomposite material in in vitro antibacterial or in vivo antibacterial drugs.

[0019] In the antibacterial application of selenium-zinc oxide core-shell nanocomposites, when they reach the designated position, zinc oxide decomposes and the pores blocked by zinc oxide open, and nano-selenium can be slowly released through the pores to exert a synergistic antibacterial effect with zinc oxide. The slow release of selenium reduces the toxic side effects of nano-selenium and has a long-lasting antibacterial effect.

[0020] The present invention exerts the synergistic antibacterial effect of selenium and zinc oxide. After the selenium-zinc oxide core-shell nanocomposite material reaches the designated position, the zinc oxide decomposes, the pores blocked by the zinc oxide are opened, and the nano-selenium can be slowly released through the pores to exert a synergistic antibacterial effect with the zinc oxide. The selenium slow release reduces the toxic and side effects of the nano-selenium, and has a long-lasting antibacterial effect. Compared with the prior art, the present invention has the advantages of simple preparation, good biocompatibility, good antibacterial effect, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The X-ray diffraction (XRD) pattern of the Se@SiO2@ZnO core-shell nanocomposite prepared in Example 1;

[0022] Figure 2 This is a transmission electron microscope (TEM) image of the Se@SiO2@ZnO core-shell nanocomposite prepared in Example 1;

[0023] Figure 3 Element mapping diagram of Se@SiO2@ZnO core-shell nanocomposite prepared in Example 1;

[0024] Figure 4 This is a particle size distribution diagram of the Se@SiO2@ZnO core-shell nanocomposite prepared in Example 1;

[0025] Figure 5 The pore size distribution curve (A) and the isotherm curve of nitrogen adsorption and desorption (B) of the Se@SiO2@ZnO core-shell nanocomposite prepared in Example 1;

[0026] Figure 6 The drug release curves of the Se@SiO2@ZnO core-shell nanocomposite prepared in Example 1 at different values;

[0027] Figure 7This is a graph showing the in vitro biosafety assessment of the Se@SiO2@ZnO core-shell nanocomposite prepared in Example 1;

[0028] Figure 8 This is a diagram showing the in vitro antibacterial effect of the Se@SiO2@ZnO core-shell nanocomposite prepared in Example 1;

[0029] Fig. 9 This is a diagram showing the in vivo antibacterial effect of the Se@SiO2@ZnO core-shell nanocomposite prepared in Example 1. DETAILED DESCRIPTION

[0030] In order to make the present invention more clearly understood, preferred embodiments are described in detail below with reference to the accompanying drawings.

[0031] Example 1

[0032] (1)Cu 2-x Synthesis of Se: First, add 5 mL of oleic acid to a three-necked flask containing 43.5 mg of selenium powder, stir and heat to 120 ° C and pass nitrogen for 5 minutes. Then heat to 280 ° C and maintain for 30 minutes under nitrogen protection to obtain a selenium precursor solution. In another three-necked flask, 49.5 mg of cuprous chloride is dispersed in 5 mL of oleic acid and 5 mL of oleylamine, stirred and heated to 120 ° C, and passed nitrogen for 5 minutes. Then, the solution is heated to 220 ° C and maintained for 10 minutes under nitrogen protection. The Se precursor solution obtained above is quickly injected into the CuCl mixed solution and maintained at 220 ° C for 5 minutes. After the solution is quickly cooled to 60 ° C, 15 mL of ethanol is added to obtain the corresponding solution. Wash with ethanol 3 times and collect by centrifugation, and finally dispersed in 10 ml of n-hexane for subsequent use.

[0033] (2) Take 5 mL of the Cu prepared in step (1) 2-x Se n-hexane dispersion was added to the reaction bottle, and 0.9 mL of deionized water was added first, and then 3 mL of n-hexanol, 3 mL of Triton X-100 and 30 mL of n-hexane were added under stirring. After the solution became clear and transparent, 0.18 mL of tetraethyl silicate solution (TEOS) was added dropwise after 5 minutes. After another 5 minutes, 0.18 mL of ammonia solution was added dropwise. After reacting for 24 hours, the mixture was washed with ethanol several times and centrifuged, and dried at 60°C.

[0034] (3) Take 20 mL (1 g / L) of the Se@SiO2 dispersion obtained in step (2) and perform ultrasonic dispersion for 5 min. Mix 0.06 g of NaOH and 0.015 g with 13 mL of ethanol. Then add 32 mL of Se@SiO2 ethanol dispersion and stir to mix evenly. Ultrasonic treatment for 5 minutes, mechanically stir and heat to 60°C, and react for 1 hour. After the reaction is completed, wash with ethanol several times and centrifuge to obtain selenium-zinc oxide core-shell nanocomposite material (Se@SiO2@ZnO).

[0035] Example 2

[0036] Se@SiO2@ZnO composite nanomaterial degradation experiment: The Se@SiO2@ZnO nanocomposite material prepared in Example 1 was equally divided into two parts, and placed in PBS solutions of pH 6.5 and pH 7.4 respectively. Under stirring, the supernatant was collected by centrifugation at a predetermined time for ICP determination of Se concentration. The same amount of the corresponding PBS solution was added to the centrifuged product, stirring was continued, and the operation steps were repeated.

[0037] Example 3

[0038] Biosafety experiment: MC3T3-E1 cells were incubated with different concentrations of Se@SiO2@ZnO nanomaterials for 24 hours, and cell viability was detected using a CCK8 kit and an ELISA reader.

[0039] Example 4

[0040] In vitro antibacterial test: (1) PBS, (2) 20 μg / mL Se@SiO2, (3) 20 μg / mL Se@SiO2@ZnO and 1×10 6 CFU / mL of ATCC43300 Staphylococcus aureus was incubated for 4 hours. The bacterial suspension was diluted in equal proportions of 10 times, 100 times, 1000 times, 10000 times, and 100000. 100 μL of the bacterial suspension after each dilution was taken and evenly spread on the sheep blood agar plate medium. The number of colonies was recorded after incubation at 37°C for 12 hours. (Here, Se@SiO2 and Se@SiO2@ZnO are the nanocomposites prepared in Example 1)

[0041] Example 5

[0042] In vivo antibacterial experiment: Mice with femoral osteomyelitis were divided into three groups and injected locally into the knee joint cavity with (1) PBS, (2) 20 μg / mL Se@SiO2, and (3) 20 μg / mL Se@SiO2@ZnO. The therapeutic effect was evaluated by counting the bacterial colonies in the infected tissue after treatment. (Here, Se@SiO2 and Se@SiO2@ZnO are the nanocomposites prepared in Example 1).

[0043] The final product synthesized in the above-described embodiment is characterized, as shown in FIG. Figure 1-9 As shown:

[0044] Depend on Figure 1 XRD, Figure 2 Transmission electron microscopy and Figure 3 From the element distribution mapping diagram, it can be seen that Se@SiO2@ZnO nanomaterials were successfully synthesized with good dispersion.

[0045] Depend on Figure 4 From the particle size diagram, we can see that the particle size of Se@SiO2@ZnO is uniform and the average particle size is about 160-170nm.

[0046] exist Figure 5 According to the surface area measurement instrument, the maximum pore size and specific surface area of ​​Se@SiO2@ZnO are 2.5nm(A) and 20m 2 / g(B), which proves the mesoporous structure of Se@SiO2@ZnO.

[0047] Depend on Figure 6 It can be seen that compared with pH 7.4, Se@SiO2@ZnO nanomaterials release more selenium in PBS buffer solution at pH 6.5, and the release of selenium gradually increases with time. This indirectly shows that the nanocomposite material degrades under acidic conditions, and the degradation rate is faster than that under neutral conditions.

[0048] Depend on Figure 7 It can be seen that Se@SiO2@ZnO has no effect on cell viability at a concentration of 100 μg / mL, indicating that Se@SiO2@ZnO has good biosafety.

[0049] Depend on Figure 8 It can be seen that Se@SiO2 has a certain in vitro bactericidal effect, while Se@SiO2@ZnO has a better in vitro bactericidal effect, indicating that Se@SiO2@ZnO nanocomposites have excellent in vitro antibacterial effects.

[0050] Depend on Fig. 9It can be seen that Se@SiO2 can reduce the bacterial load in local tissues of osteomyelitis infection, and this antibacterial effect is more obvious in mice treated with Se@SiO2@ZnO, suggesting that Se@SiO2@ZnO nanocomposites have excellent in vivo antibacterial effects.

Claims

1. A method for preparing a porous selenium-zinc oxide core-shell nanocomposite material, characterized in that: The following steps are involved: Step 1): oleic acid and selenium powder are mixed to obtain a Se precursor solution, CuCl is dispersed in oleic acid and oleylamine to obtain a CuCl mixed solution, the Se precursor solution is injected into the CuCl mixed solution, ethanol is added after the reaction, the mixture is washed with ethanol and collected by centrifugation, and dispersed in n-hexane to obtain Cu 2-x Se n-hexane dispersion; Step 2): Cu 2-x Deionized water, n-hexanol, Triton X-100 and n-hexane were added to the Se n-hexane dispersion. After the solution became clear, tetraethyl silicate solution and ammonia water were added dropwise. After the reaction was completed, the dispersion was washed with ethanol, centrifuged and dried to obtain Se@SiO2 nano core-shell particles. Step 3): dispersing Se@SiO2 nano core-shell particles in ethanol to prepare Se@SiO2 ethanol dispersion; Step 4): NaOH, zinc acetate and ethanol are mixed, and then Se@SiO2 ethanol dispersion is added, stirred, ultrasonicated, heated for reaction, centrifuged and washed to obtain a selenium-zinc oxide core-shell nanocomposite material.

2. The method for preparing the porous selenium-zinc oxide core-shell nanocomposite material according to claim 1, characterized in that: In the step 1), Cu 2-x The concentration of Se n-hexane dispersion is 10 to 800 mg / mL.

3. The method for preparing the porous selenium-zinc oxide core-shell nanocomposite material according to claim 1, characterized in that: In the step 2), Cu 2-x The volume ratio of Se n-hexane dispersion, deionized water, n-hexanol, Triton X-100, n-hexane, tetraethyl silicate solution and ammonia water is 10: 0.01-2: 1-10: 1-10: 5-100: 2-0.05: 2-0.01, and the mass concentration of ammonia water is 25-28%.

4. The method for preparing the porous selenium-zinc oxide core-shell nanocomposite material according to claim 1, characterized in that: In the step 3), the concentration of the Se@SiO2 ethanol dispersion is 0.5-10 g / L.

5. The method for preparing the porous selenium-zinc oxide core-shell nanocomposite material according to claim 1, characterized in that: In the step 4), the ratio of NaOH, zinc acetate, ethanol, and Se@SiO2 ethanol dispersion is 0.1-1 g: 0.2-2 g: 5-200 mL: 10-300 mL.

6. The method for preparing the porous selenium-zinc oxide core-shell nanocomposite material according to claim 1, characterized in that: In the step 4), the ultrasonication time is 1 to 10 minutes.

7. The method for preparing the porous selenium-zinc oxide core-shell nanocomposite material according to claim 1, characterized in that: In the step 4), the heating reaction temperature is 40 to 76° C. and the time is 0.5 to 12 hours.

8. A porous selenium-zinc oxide core-shell nanocomposite material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The selenium-zinc oxide core-shell nanocomposite material is a composite structure in which zinc oxide covers silicon dioxide spheres, and silicon dioxide spheres cover elemental Se.

9. Use of the porous selenium-zinc oxide core-shell nanocomposite material according to claim 8 in in vitro antibacterial or in vivo antibacterial drugs.